2012
DOI: 10.1088/2043-6262/3/2/025013
|View full text |Cite
|
Sign up to set email alerts
|

Towards the use of protein A-tagged gold nanoparticles for signal amplification of electrochemical immunosensors in virus detection

Abstract: In this paper we represent a study on the potential use of protein A-tagged gold nanoparticles applied for signal amplification of electrochemical immunosensors. Gold nanoparticles (GNPs) were synthesized by the chemical reduction of tetrachloroauric (III) acid trihydrate using sodium ascorbate, and then tagged with protein A (PrA) via ultracentrifugation. UV-Vis spectroscopy and transmission electron microscopy were used to verify the characteristics of formed GNPs/PrA complex. The analyzed results indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Recently, several attempts have been made to control infectious pathogens and contaminations, such as development of biosensing methods for rapid detection of infectious viruses. Electrochemical DNA biosensors and immunosensors were successfully used for detection of a variety of viral pathogens such as herpes virus, Japanese encephalitis virus, or influenza A-type virus [21][22][23][24]. In addition to virus contamination detection, bacterial/viral inactivation is an option to reduce infection risk and prevention of outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several attempts have been made to control infectious pathogens and contaminations, such as development of biosensing methods for rapid detection of infectious viruses. Electrochemical DNA biosensors and immunosensors were successfully used for detection of a variety of viral pathogens such as herpes virus, Japanese encephalitis virus, or influenza A-type virus [21][22][23][24]. In addition to virus contamination detection, bacterial/viral inactivation is an option to reduce infection risk and prevention of outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…Only one year 2012 eleven articles [1][2][3][4][5][6][7][8][9][10][11] have been published. In reference Ha P T et al [1] presented the results of their research on paclitaxel-loaded poly(lactide)-d-α-tocopheryl polyethylene glycol 1000 succinate (PLA-TPGS) nanoparticles prepared by a modified solvent extraction/evaporation technique.…”
Section: Scientific Achievementsmentioning
confidence: 99%
“…The authors experimentally demonstrated the ability of paclitaxel-loaded PLA-TPGS nanoparticles to induce apoptosis in human hepatocellular carcinoma cell lines (Hep-G2), indication the potential application of these nanoparticles as a cancer chemotherapeutic agent. In reference Dang M C et al [2] reported on the fabrication of a nanoparticle formulation of ketoprofen (Keto)-encapsulated cucurbit [6] (CB [6]) uril nanoparticles, the evaluation of its in vitro dissolution and the investigation of its in vivo pharmaceutical property. The CB [6]-Keto nanoparticles were prepared by emulsion solvent evaporation method.…”
Section: Scientific Achievementsmentioning
confidence: 99%
See 2 more Smart Citations